Nutritional status and dietary pattern of the elderly in Thulamela Municipality of Vhembe District - Selekane A. Motadi; Tshifhiwa Khorommbi; Lungile Maluleke; Anzani Mugware; Lindelani Mushaph (African Journal of Primary Health Care & Family Medicine, 2022)
Background: Dietary patterns provide comprehensive information about the food consumption habits within a population and how an individual’s dietary pattern may change with age.